Distribution and The Habitat Characteristics of Anopheles vagus (Diptera: Culicidae) Larvae at Paddy Fields in The Vicinity of Dramaga IPB University Campus Dramaga Bogor West Java - Dimas Novianto; Syifa Alya; Upik Kesumawati Hadi; Susi Soviana (Acta VETERINARIA Indonesiana, 2021)
Dramaga sub-district is an area that has rice fields close to buffalo stalls and a population of wild Macaca fascicularis as natural hosts for several species of Plasmodium. This causes the Dramaga sub-district to become a potential vector habitat for malaria, including Anopheles vagus. This study aims to analyze distribution of An. vagus larval stage in 4 villages (Cikarawang, Babakan, Margajaya, and Ciherang) in Dramaga subdistrict which have paddy field areas. Larvae were collected using a dipper, and each collection sites of the larvae habitat were marked using Global Positioning System. The physical characteristics of the water habitat measured were temperature, pH, total dissolved solids and the electrical conductivity of the water. Pearson's correlation test was used to analyze the relationship between the number of larvae An. vagus with each of the parameters water physical characteristics. The results of this study obtained 309 An. vagus larvae from the 27 collection points. Larvae of An. vagus was found in 3 villages (i.e. Cikarawang, Babakan and Ciherang), but was not found in Margajaya village. The habitat characteristics of An. vagus in paddy fields showed a water temperature of 26.6-31.7oC, pH 6.40-8.10, the total dissolved solid 36-285 ppm, and the electrical conductivity 72-262 μm/cm. The Pearsons correlation test results did not show a significant difference between the number of An. vagus larvae and each parameter (r= -0.26, 0.13, -0.15 and -0.16, respectively). The presence of An. vagus in this area could be considered in malaria vector control programs.